Don Juan DeMarco - Leven, Jeremy; Brando, Marlon; Dunaway, Faye; Depp, Johnny; Kamen, Michael ([Los Angeles, Calif.] : New Line Home Entertainment, 2004)
A psychiatrist treats a young man who believes he is Don Juan, the greatest lover of all time.
Originally released as a motion picture in 1995.
Features: previews, Bryan Adams video, isolated stereo. audio track, biographies, filmographies, interactive menus, scene selection.
Director of photography, Ralf Bode; production design, Sharon Seymour; film editor, Tony Gibbs; music, Michael Kamin.
Marlon Brando, Johnny Depp, Faye Dunaway, Rachel Ticotin, Bob Dishy.
MPAA rating: PG-13.
DVD, Dolby digital 5.1 surround.
Keywords: Don Juan (Legendary character) -- Drama; Delusions -- Drama; Mentally ill -- Drama; Video recordings for hard of hearing people; Feature films; Comedy films